Hubungan Status Gizi dengan Rata-Rata Usia Menarche - Ema Nur Fitriana; Annang Giri Moelyo; Istar Yuliadi (Nexus Kedokteran Komunitas, 2012)
Background : Menarche is the first menstrual period in woman reproduction cycle. Several epidemiology studies shows that the onset of menarche was became earlier. This condition was supposed to be related with the increases of nutritional status. The aim of this study was to identify the association between Nutritional status with the mean of age of menarche in SD N 1 Kleco Surakarta (elementary school) students. Method : An analytical observational study using a cross sectional design, was performed in SDN 1 Kleco Surakarta (elementary school) students within the onset of menarche or the 3rd-6th grades student on April 2012. Nutritional status was measured anthropometically for calculating and plotting the body mass index (BMI) for age based on CDC 2000 growth chart. An interview was done to know the age of menarche. The association between nutritional status with the mean age of menarche had been analyzed by Kruskal Wallis SPSS 17 for windows, meanwhile the association between nutritional status with episode of menarche had been analyzed by Chi Square. Result : This study shows 48 (26,8%) subjects were underweight, 96 (53,6%) subject were normal, 25 (13,9%) subject were overweight, and 10 (5,7%) subject were obese. Twenty six subjects (14.5%) have had period of menarche when we did this study. Means of age of menarche is 10.72 (SD 0.89) years old; the youngest age of menarche is 9 years old (2 subjects, 7.7%). Chi-square test showed no association between nutritional status and episode of age of menarche (odd ratio 1.64, 95%CI 0.63-4.39). Kruskall-Wallis test revealed no association between overweight-obese girls and means of age of menarche (p =0.906,p>0.05). Conclusion : There is no association between nutritional status with the mean of age of menarche in SD Negeri 1 Kleco Surakartas student. Keywords: Nutritional Status - Age of Menarche